2020
DOI: 10.1111/jpn.13393
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome changes associated with fat deposition in the longissimus thoracis of Korean cattle following castration

Abstract: Castration is a reliable method of increasing the intramuscular fat (IMF) content (marbling) of the longissimus thoracis (LT) muscle (Bong

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Complement systems and coagulation cascades might play a vital role in post-trauma and subsequent inflammatory reactions as innate immunity elements [ 41 ]. A previous study observed greater IMF deposition in Korean cattle after castration, which might lead to alterations in the complement and coagulation cascade pathways, possibly owing to obesity and the subsequent inflammation [ 42 ]. Platelet activation is regulated by the complement system, and platelet activity is mostly linked to the start of coagulation cascades [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complement systems and coagulation cascades might play a vital role in post-trauma and subsequent inflammatory reactions as innate immunity elements [ 41 ]. A previous study observed greater IMF deposition in Korean cattle after castration, which might lead to alterations in the complement and coagulation cascade pathways, possibly owing to obesity and the subsequent inflammation [ 42 ]. Platelet activation is regulated by the complement system, and platelet activity is mostly linked to the start of coagulation cascades [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Castration upregulated the transcriptomes involved in lipid metabolism, including adipogenesis, fatty-acid-synthesis/-esterification and fatty-acid-oxidation, tricarboxylic-acid-cycle, and oxidative-phosphorylation genes [ 79 ]. We also applied RNA-sequencing analysis to examine transcriptomic changes in Korean cattle bulls following castration and found that the transcriptomes involved in known pathways such as peroxisome proliferator-activated receptor signaling and retinol metabolism changed in the LM [ 80 ]. We also found that the transcriptomes of novel pathways such as the complement and coagulation cascades are changed.…”
Section: Mechanisms Of Intramuscular Adipose Tissue Depositionmentioning
confidence: 99%
“…High-throughput RNA sequencing is a powerful tool for quantifying transcripts [ 7 ]. Several RNA sequencing studies have examined the molecular mechanisms of IMF deposition and identified differentially expressed genes (DEGs) between different IMF levels in the LT of cattle [ 8 , 9 ]. The molecular mechanisms responsible for marbling fineness are unknown.…”
Section: Introductionmentioning
confidence: 99%